LB0001 Baricitinib, an Oral Janus Kinase (JAK)1/JAK2 Inhibitor, in Patients with Active Rheumatoid Arthritis (RA) and An Inadequate Response to CDMARD Therapy: Results of the Phase 3 RA-Build Study. (9th June 2015) - Dougados, M.; van der Heijde, D.; Chen, Y.-C.; Greenwald, M.; Drescher, E.; Liu, J.; Beattie, S.; de la Torre, I.; Rooney, T.; Schlichting, D.; de Bono, S.; Emery, P.
Abstract : Background: In ph 2 studies, baricitinib (bari) improved disease activity with an acceptable safety profile in patients (pts) with active RA and inadequate response (IR) to conventional DMARDs (cDMARDs). Objectives: To report results from a 24-week (Wk) global ph 3 study of bari in pts with active RA and an IR or intolerance to ≥1 cDMARD. Methods: Pts with active RA (TJC & SJC≥6 & hsCRP≥3.6 mg/L) with stable background treatment were randomized 1:1:1 to placebo (PBO) or bari (2 or 4 mg) QD, stratified by region and baseline joint erosion status, with rescue from Wk 16 for nonresponders. Primary endpoint was ACR20 response at Wk 12 for bari 4 mg vs. PBO. Results: Of 684 randomized pts, 81% were seropositive with mean baseline DAS28 of 5.55 (-hsCRP) and 6.22 (-ESR). Rescue rates were 9%, 7%, and 24% for bari 2 mg, 4 mg, PBO, respectively. ACR20 response at Wk 12 was 62% with bari 4 mg vs. 40% with PBO (p≤0.001). Improvements in ACR50, ACR70, DAS28, CDAI, SDAI, and HAQ-DI were seen (Table ), many as early as Wk 1. Change in mTSS at Wk 24 was lower with bari 2 or 4 mg vs. PBO (p≤0.05, p≤0.01, respectively). TEAE and SAE rates, including serious infections, were similar among pts receiving bari 2 or 4 mg or PBO (SAEs: 3%, 5%, 5%, respectively). There were no GI perforations or opportunistic infections. In the bari 4 mg group, 1 TB case and 1 NMSC case occurred. In the PBO group, 2 deaths and 2 MACE occurred. Lab findings were similar to ph 2; few abnormalities led to discontinuation. Conclusions: Once daily oral bari was associated with rapid and sustained clinical improvement and inhibition of radiographic joint damage, with an acceptable safety and tolerability profile. The most robust benefit across measures was seen with the 4 mg dose. Disclosure of Interest: M. Dougados Grant/research support from: Eli Lilly and Company, AbbVie, Pfizer, UCB, Bristol-Myers Squibb, Novartis, Sanofi, and Roche, Consultant for: Eli Lilly and Company, AbbVie, Pfizer, UCB, Bristol-Myers Squibb, Novartis, Sanofi, and Roche, D. van der Heijde Consultant for: AbbVie, Amgen, AstraZeneca, Augurex, Bristol-Myers Squibb, Boehringer Ingelheim, Celgene, Centocor, Chugai, Covagen, Daiichi, Eli Lilly and Company, Galapagos, GSK, Janssen Biologics, Merck, Novartis, Novo-Nordisk, Otsuka, Pfizer, Roche, Sanofi-Aventis, UCB, and Vertex, Y.-C. Chen Grant/research support from: Eli Lilly and Company, Speakers bureau: Eli Lilly and Company, AbbVie, Pfizer, and Bristol-Myers Squibb, M. Greenwald Grant/research support from: Eli Lilly and Company, E. Drescher: None declared, J. Liu Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, S. Beattie Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, I. de la Torre Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, T. Rooney Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, D. Schlichting Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, S. de Bono Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, P. Emery Consultant for: Abbott/AbbVie, Bristol-Myers Squibb, Pfizer, UCB, MSD, Roche, Novartis, Samsung, Takeda, and Eli Lilly and Company